Analisis Peranan Mahasiswa KKN UINSU dalam Membangun Peningkatan UMKM dengan Pendekatan Ekonomi dan Teknologi Informasi di Desa Lau Buluh Kecamatan Kuta Buluh - Abdul Malik Karim Amrullah; Agustami Daulay; Nadita Syahfrida; Noni Artiya Syahputri; Nuriza Dora (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to examine in depth the contribution of UINSU Community Service Program (KKN) students in developing Micro, Small, and Medium Enterprises (MSMEs) in Lau Buluh Village by using economic approaches and information technology. Through mentoring, training, and community empowerment activities, students play a crucial role in helping MSMEs manage their businesses in a more focused manner. This role includes assistance in business planning, administrative management, improving marketing strategies, and implementing digital technology in daily business activities. One of the students' tangible contributions is seen in the use of social media as a means of product promotion, which can expand the market reach beyond the village area. In addition, students are also introduced to a simple financial recording application so that MSMEs can manage cash flow more regularly and transparently. This program has had a positive impact in terms of increasing knowledge, skills, and awareness of business actors regarding the importance of innovation in maintaining business continuity. Although there are still obstacles, especially in adapting to the use of digital technology, the results obtained indicate that there is a significant opportunity to develop digital-based MSMEs at the village level. Thus, this study confirms that KKN students have a strategic role as agents of change in strengthening the economic empowerment of rural communities.